Karakteristik Morfologi Tanaman Selada Menggunakan Pengolahan Citra Digital - Akhmad Fadjeri; Bayu Aji Saputra; Dicki Kusuma Adri Ariyanto; Lisna Kurniatin (STMIK Sinar Nusantara, 2022)
The aim of this study is to find out characteristics of Green Rapid lettuce with digital image processing using morphological technique on image and first order statistical feature extraction. In digital image processing, the original images were processed to be RGB image and then processed again to be grayscale one. The grayscale images were processed to be biner image so that the image can be changed into biner form (0 and 1). In morphological process, this study used edge detection, dilation, and erosion. The final stage of morphological process used feature extraction process to find out image morphological characteristics which can be described mathematically. The result of extraction showed its samples within range or average area about 9.593.622.205.915.820 pixels, perimeter about 8.427.724.410.694.360 pixels, length about 829.877.174.308.893 pixels, and width about 1.654.002.663.010.820 pixels